Non-vitamin K antagonist oral anticoagulants versus warfarin in atrial fibrillation patients with heart failure and preserved, mildly reduced, and reduced ejection fraction: A systemic review and meta-analysis - Wulamiding, Kaisaier; Xu, Zixuan; Chen, Yili; He, Jiangui; Wu, Zexuan (Frontiers in Cardiovascular Medicine, 2022)
Background Patient prevalence of atrial fibrillation (AF) and heart failure (HF) is increasing, and anticoagulation for patients from heterogeneous backgrounds with both conditions remains controversial. In this meta-analysis, we are aiming to compare the effectiveness and safety of the non-vitamin K antagonist oral anticoagulants (NOACs) and warfarin in AF patients with HF and preserved (HFpEF), mildly reduced (HFmrEF), and reduced (HFrEF) ejection fraction. Methods and results We systematically searched the PubMed, Cochrane, and Embase databases until January 2022. The primary effectiveness and safety outcomes were stroke or systemic embolism (SSE) and major bleeding, respectively. We abstracted risk ratios (RR) and 95% confidence intervals (CIs) and compiled them using a random-effects model. We analyzed data of 266,291 patients from 10 studies. By comparing NOACs with warfarin, patients with AF and HF have reduced the risk of SSE (RR: 0.83, 95% CI 0.76–0.91), all-cause mortality (RR: 0.85, 95% CI 0.80–0.91), major bleeding (RR: 0.79, 95% CI 0.69–0.90), and intracranial hemorrhage (RR: 0.54, 95% CI 0.46–0.63). Further analyses based on the HF subtypes showed that NOACs reduced the chances of SSE (RR: 0.71, 95% CI 0.53–0.94) in the HFrEF group and major bleeding (RR: 0.74, 95% CI 0.57–0.95) in HFmrEF and HFpEF groups. There were no differences regarding SSE (RR: 0.91, 95% CI 0.76–1.09) in HFmrEF and HFpEF groups and major bleeding (RR: 0.99, 95% CI 0.79–1.23) in the HFrEF group. Conclusion For patients with AF and HF, NOACs have better or similar effectiveness and safety than warfarin, but the stroke prevention superiority of NOACs over warfarin varies in different HF subtypes.